The Role of Counselors for Special Needs Children with Attention Hyperactivity Disorder in Inclusion Schools - Fitriyani, Fitriyani; Sari, Arilda Fitria; Sari, Elsa Nurmala (ALACRITY : Journal of Education, 2024)
Children with special needs with Attention Deficit Hyperactivity Disorder (ADHD) and autism have unique challenges in their development and learning. Children with ADHD often have difficulty focusing and difficulty communicating, social interaction and difficulty controlling behavior in structured environments such as schools. The benefit of this study is to find out how far away counselors play in inclusion schools. This research method or approach uses observations, interviews with counselors, and accompanying teachers at the Al-Jannah Islamic School of Science. The purpose of this study was to find out how a counselor or a co-teacher who handles the school's crew members and supports the school in developing an inclusive learning program. The result obtained from this study is that the role of a counselor or a companion teacher is very important in helping children with special needs (ABK) adapt in the school environment.